Streptococcus pneumoniae associated hemolytic uremic syndrome in children - Young, Heather L.; Brown, Clare C.; Crawford, Brendan; Blaszak, Richard T.; Prodhan, Parthak (Frontiers in Pediatrics, 2023)
Introduction Previous small-scale, single-center investigations of Streptococcus pneumoniae associated hemolytic uremic syndrome (SpHUS) have shown increased disease severity among SpHUS relative to non-SpHUS patients. Our study compares the impact of S. pneumoniae on patient outcomes between SpHUS cases and non-SpHUS controls using the national, multicenter retrospective Pediatric Health Information Systems (PHIS) Database. Methods Children <18 years of age with a diagnosis of HUS were included. Univariate analyses and multivariable linear and logistic regressions were utilized to assess the impact of S. pneumoniae on mortality, length of stay (LOS), intensive care unit admission (ICU), and mechanical ventilation use. Models were adjusted for demographic and clinical characteristics, including cardiac, neurologic, pulmonary, gastrointestinal, immunologic and renal clinical complications. Results Of 3,952 index HUS hospitalizations, 231 (5.8%) were due to SpHUS. SpHUS patients had worse outcomes, including longer hospital stays, increased rate of ICU admission, and increased use of mechanical ventilation (p < 0.001 for all). There was a strong positive relationship between clinical complications and adverse outcomes. After adjusting for covariates, SpHUS was associated with an increase in hospital LOS by 3.47 days (p = 0.009) and overall ICU-LOS by 4.21 days (p < 0.001). SpHUS was also associated with increased likelihood of mechanical ventilation (OR: 3.08; p < 0.001), with no increase in ICU admission (p = 0.070) and in-hospital mortality (p = 0.3874). Discussion Our study highlights that SpHUS patients are at increased risk of multiple adverse outcomes likely due to the summative impact of pneumococcal infection and HUS as well as more frequent clinical complications.